Improving Wind Environment of Residential Neighborhoods by Understanding the Relationship between Building Layouts and Ventilation Efficiency. (May 2017) - You, Wei; Shen, Jialei; Ding, Wowo
Abstract: This research attempts to probe into the correlation between the residential building layout and ventilation performance of various spaces in an operative level. To quantify the influence of design change on outdoor ventilation, numerical modeling technology is adopted with ANSYS-Fluent as the simulation tool. As to evaluate the ventilation efficiency of exterior space, local mean age of air (L-MAA), which is common used in recent urban form studies, is further discussed for local region's ventilation efficiency in residential neighborhoods. Using this ventilation index, several cases are calculated and three types of building layout changes (lateral spacing, building lengths and stagger of location) are discussed. The simulation results show that L-MAA is a useful ventilation index to access the design changes on urban space ventilation and these design changes have great effects on exterior space ventilation. Building length has great influence on ventilation efficiency of different spaces, while the influence of lateral spacing and stagger of location changes varies greatly in different local regions.